Needs Tokoh Izumi Kudo Dalam Film Narratage: Teori Personologi Henry Murray - Sukma Ayu Agustin; Sri Oemiati (KIRYOKU, 2026)
This research aims to describe the needs of the character Izumi Kudo in the film Narratage with Henry Murray's personology theory, which states that need is a mental drive formed from brain activity in regulating perception, thought, and action to overcome unsatisfactory conditions, generally influenced by environmental factors accompanied by certain emotions. The focus of the research is the needs of the character Izumi, who is involved in a complicated relationship with Hayama Takashi, which is influenced by differences in age and social status. The research method used is descriptive qualitative with observation techniques and documentation of scenes and dialogues. The results show that Izumi Kudo has six needs according to Henry Murray: inavoidance, affiliation, succorance, deference, nurturance, and sex. The conclusion of this study is that Izumi's personality is not driven by a single need, but rather by a series of complementary needs, thus shaping Izumi's identity and life journey in the film Narratage.